The firm and the self-enforcing dynamics of crime and protection - Eva Kløve; Halvor Mehlum (University of Oslo, Department of Economics, 2017)
We model the symbiotic relationship between criminals and a partnership of protection providers - the Firm. In the absence of state authority, insecurity and crime generate a demand for protection. When the protection providers themselves are recruited among criminals, the prospect of graduating to the Firm magnifies the incentive for violent crime. More violence in turn increases the income of the protection providers. The result is a violence multiplier. Combining elements from tournament and rent-seeking theory, we derive results that contrast with standard results from the rent-seeking literature. For example, a decrease in the cost of violence increases violence more than pari passu and increases the value of being a criminal. The violence multiplier also generates an incentive for the protection providers to welcome new partners into the Firm. This is a crucial premise in explaining the viability of many violent structures. We confirm empirical relevance of key elements of our framework by exploring unique data on incarcerated youth in South Africa.
Keywords: H1; K0; L8; 330; Organized crime; violence